Killing faith [videorecording (DVD)] - Crowley, Ned; Pearce, Guy; Wise, DeWanda; Pullman, Bill (Shout! Factory, 2025)
Set against the vast plague-ravaged deserts of the 1849 Arizona Territory, Killing Faith is a haunting journey through the American West a land of sickness, violence, and whispers of something darker to a land of deliverance.